A urine test for bladder cancer: available soon in primary care?. Issue 4 (29th July 2020) - di Martino, Erica; Ayaz‐Shah, Anam; Shinkins, Bethany; Jain, Sunjay; Neal, Richard D
Abstract : Several point‐of‐care urine tests have been developed to help identify patients who may be at higher risk of bladder cancer. Here the authors look at their potential to aid triage of patients with haematuria in primary care.